3D-printed Patient-specific Guides for Hip Arthroplasty. Issue 16 (15th August 2018) - Henckel, Johann; Holme, Thomas J.; Radford, Warwick; Skinner, John A.; Hart, Alister J.
Abstract : Surgeons and engineers constantly search for methods to improve the surgical positioning of implants used for joint arthroplasty. Rapid prototyping is being used to develop patient-specific instrumentation (PSI) and has already been successfully translated into large-scale clinical use for knee arthroplasty. PSI has been used in shoulder arthroplasty; however, it is not yet known whether PSI provides improved accuracy and outcomes compared with conventional methods in either shoulder arthroplasty or knee arthroplasty. In the hip, PSI has been limited to the positioning of custom-manufactured implants and a small number of surgeons testing the emerging solutions from different manufacturers. Early results indicate consistent accurate positioning of implants with the use of PSI in hip arthroplasty but with added costs and uncertain effect on clinical outcomes.